In vitro study of anti-Helicobacter pylori activity of honey: a systematic review - Adam Quraisiah,; Annuar Fazalda,; Alfizah Hanafiah,; Nur Azlina Mohd Fahami, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This review explores the beneficial effects of honey on Helicobacter pylori-induced gastric ulcer and duodenal ulcer. The research of the effectiveness of honey on H. pylori infection using electronic databases was done, these include Medline via Ovid Medline, Scopus and ScienceDirect published from the year 2000 to 2018. The articles were evaluated and selected based on the criteria which report on the effects of honey on gastric ulcer and duodenum ulcer caused by H. pylori infection. There are 53 articles were identified, which stated to the studies that relate to the criteria. Afterwards, nine articles on honey and its extracts were selected and assessed accordingly in this review. All studies reported positive effects of honey on H. pylori-induced gastric ulcer and duodenal ulcer. Most of the studies showed at minimum 10% of honey concentration were effective as anti-H. pylori activity. This systematic review emphasized the potential of honey used to inhibit the H. pylori infection in-vitro. Future extensive studies are required to find the active component and molecular mechanism of honey before animal and human observational studies could be conducted to deliver valid evidence.